A Fast and Sustainable Route to Bassanite Nanocrystals from Gypsum. (6th February 2022) - Maslyk, Marcel; Dallos, Zsolt; Koziol, Martha; Seiffert, Sebastian; Hieke, Tim; Petrović, Katharina; Kolb, Ute; Mondeshki, Mihail; Tremel, Wolfgang
Abstract: Calcium sulfate is an important construction material. More than 1600 million square meters of interior surfaces are covered with plasterboards in Europe each year. Plasterboard is manufactured by transforming mined or recycled gypsum (CaSO4  × 2 H2 O) to bassanite (CaSO4  × ½H2 O) in a time‐ and energy‐consuming heating process. A fast and sustainable way to produce bassanite by solvent‐assisted milling, thereby eliminating the need for energy‐intensive dehydration, is described. The milling reaction is complete after ≈200 min. Kinetic studies revealed that gypsum crystals transform to bassanite by shear forces during milling. 1 H nuclear magnetic resonance (NMR) spectroscopic techniques and Fourier‐transform infrared spectroscopy (FT‐IR) show that the resulting bassanite nanocrystals are stabilized by surface functionalization with the auxiliary solvent methanol. Bassanite particles produced over extended milling times of 990 min form long‐term stable dispersions without stabilizers and no signs of precipitation. Addition of water to bassanite leads to instant agglomeration, followed by a phase change to gypsum. The dispersibility in volatile methanol and the elucidation of the crystallization mechanism allow also for applications of the bassanite nanocrystals in hybrid materials. Abstract : Solvent‐assisted ball milling of gypsum leads to the formation of bassanite nanocrystals enabling the formation of a binder material without high‐temperature calcination and emission of CO2 .